Supporting early career anatomists: An international challenge - Hartmann, Carol; du Toit, F.; Hutchinson, E.; Pather, N.; Kramer, Beverley (My University, 2023)
Introduction: The formative years in academia are difficult for early career academics as they transition into their new roles in teaching and research. Ubiquitous changes in health sciences education have compounded this transition for early career anatomists (ECA), who must balance curriculum transformations, research imperatives and administrative responsibilities as they navigate their transition. Support for ECAs is thus important in order to provide a strong pipeline of anatomists for the future of the discipline and its foundational role in the health sciences. Thus, this study investigated the needs of international ECAs with respect to teaching, research and career/professional development in the anatomical sciences. Method: The authors distributed an online survey in 2018 to ECAs of member associations of the International Federation of Association of Anatomists (IFAA). The survey contained both closed and open-ended response questions. Data gathered included ECAs level of academic appointment, training for teaching and nature of support that ECAs may find valuable for their development as anatomists. Frequencies and 95% confidence intervals were calculated and answers to open-response questions were analysed qualitatively. Results: Over 590 respondents from across the globe answered the survey. Requests for training in the clinical relevance and application of anatomical sub-disciplines were frequent. Importantly, support to establish collaborations, mentorship relationships and professional networks were repeatedly requested. Conclusion: In this first ever international survey of ECAs, the needs expressed by respondents indicate the importance of academic and professional development support at both local and global levels. Partnerships between the IFAA, institutions, anatomical and educational associations should create training and mentoring opportunities to smooth the transition into academia for these young academics, which would ensure the future of the discipline and its role in the health sciences.
Keywords: SDG-4: Quality education